Motor disorder suggestive of vagal indigestion in goat - Case report - Simões, Sara Vilar Dantas; de Lira, Milena Áquila Aragão; Neto, Eldinê Gomes de Miranda; Pessoa, Clarice Ricardo de Macêdo; de Medeiros, Gildenor Xavier; Medeiros, João Marcos de Araújo (Brazilian Journal of Veterinary Medicine, 2014)
ABSTRACT. Simões S.V.D., Lira M.A.A., Miranda Neto E.G., Pessoa C.M.R., Medeiros G.X. & Medeiros J.M.A. [Motor disorder suggestive of vagal indigestion in goat - Case report.] Transtorno motor sugestivo de indigestão vagal em caprino - Relato de caso. Revista Brasileira de Medicina Veterinária, 36(1):101-104, 2014. Programa de Pós-Graduação em Medicina Veterinária, Centro de Saúde e Tecnologia Rural, Universidade Federal de Campina Grande, Campus de Patos, Avenida Universitária s/n, Bairro Santa Cecília, Patos, PB 58708-110, Brasil. E-mail: aquilavet@yahoo.com.br A case of motor disorder suggestive of vagus indigestion in goat is described. The clinical signs were apathy, weight loss, dehydration, bradycardia, distention and hypermotility ruminal. Adherences were observed in abdominal cavity during laparotomy. At necropsy were observed adherences of the visceral pleura of the liver to the diaphragm and abscesses in organs as liver, spleen and in the cranial area to the retículo. These finds suggest that branches of the vague nerves were involved in the inflammatory process and caused a similar disturb observed as Hoflund syndrome in bovines.